Enhanced accuracy and high sensitivity in dielectric characterization through a compact and miniaturized metamaterial inspired microwave sensor - Al Gburi, Ahmed Jamal Abdullah; Singh, Kunal Kumar; Singh, Ajit Kumar; Mahto, Santosh Kumar; Sinha, Rashmi (Elsevier B.V., 2024)
This academic paper introduces a novel sensor known as the Planar Microstrip-based Triple Ring Bridge Complementary Split Ring Resonator (TRB-CSRR) sensor. The main objective of this sensor is to determine the permittivity and thickness of solid dielectric substances. The TRB-CSRR sensor is meticulously designed to resonate precisely at a frequency of 4.86 GHz, achieving a significant notch depth of −33.5 dB. This configuration displays an enhanced average relative sensitivity of 20.2%. The study undertakes numerical assessments across various scenarios, encompassing situations where the sensor interacts with diverse dielectric materials. These assessments yield insights into alterations in resonant frequencies. By meticulously refining the design, the sensor's capability to confine electric fields precisely at the resonant frequency is amplified, ultimately resulting in heightened sensitivity towards dielectric characteristics. The sensor's efficacy is tested using materials featuring relative permittivity values spanning from 1.006 to 12.9, while consistently adhering to dimensions of 5 mm×5 mm×1.6 mm. To validate the conceptual frame-work, a physical sensor is fabricated, and its response is gauged through the utilization of a vector network analyzer (VNA-AV3672D). Employing curve fitting methodologies, alterations in resonance frequencies due to interactions with the tested materials are presented, underscoring the impact of permittivity and thickness. The outcomes derived from simulations, empirical measurements, and calculations display a robust alignment.